Gyömrői gyilkosságok - Kisfaludy, András (Hungary, 2003)
Following WW2 Gyomro was the scene of one of Hungary's biggest political murder series. It only became possible to investigate the cases after 1989. Survivors and relatives talk about the systematic cleansing of intellectuals and everyone who looked like one.
Keywords: Documentary films